ROLE OF CURCUMA ZEDOARIA EXTRACT ON PLACENTAL GROWTH FACTOR (PLGF) IN DIABETIC RETINOPATHY WHITE WISTAR RATS - Ong, Gabriella Fransisca; Rusip, Gusbakti; Chiuman, Linda; Sulistijanto, Eddy; Tarigan, Elviyanti (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Diabetic retinopathy is damage to retinal capillaries in diabetics that can cause visual impairment, ranging from mild to permanent blindness. This study aims to analyze the effect of Curcuma zedoaria (temu putih) extract on placental growth factor (PLGF) levels in white Wistar rats with diabetic retinopathy. The research design used post-test only control group, involving six groups of wistar rats with five heads each. Data were analyzed using Oneway ANOVA and t-test. The results showed that the administration of Curcuma zedoaria extract at a dose of 500 mg/kgBB had the greatest effect on reducing PLGF in diabetic retinopathy rats. For reducing blood sugar levels (KGD), a dose of 7500 mg/kgBB proved to be the most effective. However, no significant relationship was found between PLGF levels and retinal histopathology results. Most of the rats had a retinal score of 0, which means no inflammatory cells were found in the retinal layer (0 cells/visual field). There were rats with a retinal score of 1, namely rats that received doses of 250 mg/kgBB and 500 mg/kgBB. In this score, inflammation was found in the outer plexiform layer (OPL). In addition, there were rats with a retinal score of 2 at a dose of 250 mg/kgBB, which also showed the distribution of inflammation in the OPL layer. In this study, Curcuma zedoaria extract can reduce PLGF and KGD in Wistar rats with diabetic retinopathy, although its effect on improving retinal histopathology is still limited.